Kontribusi Pemerintah Kota Bitung dalam Memajukan Pendidikan Non-Formal melalui Bantuan Sosial kepada PKBM - Karouw, Rizky Fridolin; Laksmono, Bambang Shergi (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2023)
This research illustrates how the Bitung City Government's policy through social assistance for the distribution of the implementation of non-formal education programs in the center of community learning activities in an effort to increase the level of graduation of the community in Bitung City through the Equality Examinations program. As well as how the Bitung City Government's policy related to budget assistance to the center of community learning activities can accommodate the needs of people who drop out evenly and have the same opportunity in the fulfillment of educational services in Bitung City. Thus, this research focuses on two things, namely 1) Analyzing a non -formal education budget assistance policy issued by the Bitung City Government; 2) Knowing the optimization of social assistance to the center of community learning activities for justice and equity in education for people of Bitung City. The research uses a qualitative approach with a type of descriptive research by collecting data that researchers will use, namely through: in-depth interviews, observations and documentation studies. Through this research, it is known that the Bitung City Government has tried to strengthen the non-formal education sector through social assistance in the operational budget for equitable implementation of equality education programs at the center of community learning activities; the conclusion is that the Bitung City Government must maintain the aid policy for the long term by making a Mayor Regulation Consider the number of high school dropout communities and the limitations of the community learning activity center itself.